Multipole specifications for insertion devices in LF15 - Bosch, Robert A. (My University, 2005)
Imperfections in the magnetic field of an insertion device affect the electron storage ring, thereby impacting the users of all beamlines. To minimize adverse effects, the manufacturer is required to meet specifications on the multipoles of the longitudinally integrated magnetic field. For 800-MeV ring operation in the LF15 low-emittance lattice, specifications are obtained for insertion devices located in the long straight sections and the short straight sections.
This is a 9-page document.